2001
DOI: 10.1002/car.686
|View full text |Cite
|
Sign up to set email alerts
|

Domestic violence and child abuse: developing sensitive policies and guidance

Abstract: Domestic violence is everywhere and nowhere. No statutory organization or health service has work with either perpetrators or survivors of domestic violence (usually women and children) as the primary focus of their service, yet all agencies will have very significant numbers among their clients/service users. It is therefore crucial that the policy framework is developed both within and between agencies to address the need, and scope, of intervention in this area and particularly the impact on children. Curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 8 publications
0
16
0
1
Order By: Relevance
“…Other research has found that over one-quarter of the men on death row in Trinidad and Tobago have been charged with killing their wives, girlfriends, or common-law spouses (Women and Development Studies Group, 1994). Domestic violence has also been linked to child abuse (Anaya, 2004;Humphreys et al, 2001;Jouriles et al, 2008). As such, where women are abused, other family members may also be at risk.…”
Section: Violence In the Homementioning
confidence: 99%
“…Other research has found that over one-quarter of the men on death row in Trinidad and Tobago have been charged with killing their wives, girlfriends, or common-law spouses (Women and Development Studies Group, 1994). Domestic violence has also been linked to child abuse (Anaya, 2004;Humphreys et al, 2001;Jouriles et al, 2008). As such, where women are abused, other family members may also be at risk.…”
Section: Violence In the Homementioning
confidence: 99%
“…It was clear that this was the case for the children in this study; children in the age group of six to ten years with a mother currently in prison and who had been in prison, had experienced a high level of child protection intevention as well as family fragmentation. The criminal convictions for the mothers of this group of children confirmed the pattern of substance abuse, mental health problems, family violence and child abuse and neglect noted by McGuigan and Pratt (2001), Humphreys et al (2001) and Goddard and Stanley (2004). The mothers in the study were in overwhelmingly prison for theft, drug related offences, murder (in one case) and armed robbery.…”
Section: The Children and Their Parentsmentioning
confidence: 75%
“…Whilst female prisoners represent approximately 7% of the prison population across Australia, female prisoners are generally young, and have dependent children. Life before prison for many women and their children is marked by unsettled housing, low incomes, substance abuse, mental health problems, family violence and child abuse and neglect (McGuigan and Pratt, 2001;Humphreys, Mullender, Lowe, Hague, Abrahams and Hester, 2001;Stanley and Goddard, 2004).…”
Section: Parents In Prisonmentioning
confidence: 99%
“…Indeed, Humphreys et al (2001) premise their good practice guidelines on a similar assumption: that services should be 'refocused . .…”
Section: Current Child Protection Practicementioning
confidence: 98%
“…But there is very little evidence that the changes in domestic violence guidance and legal options have affected practice to the benefit of the children concerned. Indeed, when Humphreys et al (2001) sought to survey this area, they were able only to discover what various agencies regarded as good practice rather than describe what good practice was going on. Unfortunately, the global evidence that child welfare systems can change in regard to domestic violence is scarce and pessimistic.…”
Section: Current Child Protection Practicementioning
confidence: 99%